Model Development on Awareness of Education for Sustainable Schools Development in Malaysia - Hanifah Mahat; Yazid Saleh; Mohmadisa Hashim; Nasir Nayan (Faculty of Geography, Universitas Gadjah Mada, 2016)
ἀis article aims to develope the Structural Equation Model (SEM) on Education for Sustainable Development (ESD) student awareness around Sustainable Schools in Malaysia. ἀe cluster sampling technique was used in selecting the school samples and the respondents were then also selected through simple random sampling among upper second-ary pupils. A questionnaire survey was administered for 447 pupils, to evaluate the aḀer eᴀects of the SLAAS. ἀe results showed that the model has been developed to provide an overview of each construct (knowledge on SLAAS Program, ESD content knowledge, ESD practices knowledge, attitudes of ESD and behavioral constructs of ESD) formed a ᰀt model. ἀe implication of this article showed that SLAAS Program implemented in Malaysia can be an indicator for the achievement of sustainable school.